2022
DOI: 10.1111/ijd.16042
|View full text |Cite
|
Sign up to set email alerts
|

The role of dermoscopy in the diagnosis of subungual glomus tumors

Abstract: Background and Objectives The dermoscopic features of glomus tumors have only been described in a few case reports. The aim of this research was to define the clinical and dermoscopic features of subungual glomus tumors. Methods Thirty‐two patients with subungual glomus tumors were evaluated retrospectively. Results On the photographs, longitudinal erythronychia, longitudinal leukonychia, punctate leukonychia, splinter hemorrhage, isolated capillaries, distal notching, distal subungual hyperkeratosis, onycholy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 24 publications
(67 reference statements)
4
21
1
Order By: Relevance
“…In our series, we found vessels in approximately 28% of cases (35.1% of those with a visible structureless subungual spot). The presence of vascular structures in the dermoscopic examination of SUGTs has been previously reported, ranging from 13.3% to around 50% in the largest series published to date 5,12 . As previously published by Nogueira Maheara et al ., these vessels can be better visualized if intraoperative dermoscopy is performed 18,19 .…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…In our series, we found vessels in approximately 28% of cases (35.1% of those with a visible structureless subungual spot). The presence of vascular structures in the dermoscopic examination of SUGTs has been previously reported, ranging from 13.3% to around 50% in the largest series published to date 5,12 . As previously published by Nogueira Maheara et al ., these vessels can be better visualized if intraoperative dermoscopy is performed 18,19 .…”
Section: Discussionmentioning
confidence: 63%
“…5,6,12,13 As recently published by G€ oktay et al, who observed this structure in 29/32 SUGTs (90.6%), dermoscopy can reveal this feature when it is invisible to the naked eye. 12 The histopathological explanation for this finding is the presence of a subungual unencapsulated tumour, composed by glomus cells forming nests, sheets, and trabeculae, interspersed by a variable amount of vascular channels. 1 In our series, we found vessels in approximately 28% of cases (35.1% of those with a visible structureless subungual spot).…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations